Melanocortin receptor activation alleviates amyloid pathology and glial reactivity in an Alzheimer’s disease transgenic mouse model - Jackie K. Y. Lau (Nature Portfolio, 2021)
Abstract Alzheimer’s disease (AD) is a devastating neurodegenerative disorder with no disease-modifying treatment. AD progression is characterized by cognitive decline, neuroinflammation, and accumulation of amyloid-beta (Aβ) and neurofibrillary tangles in the brain, leading to neuronal and glial dysfunctions. Neuropeptides govern diverse pathophysiological processes and represent key players in AD pathogenesis, regulating synaptic plasticity, glial cell functions and amyloid pathology. Activation of the pro-opiomelanocortin (POMC)-derived neuropeptide and its receptor from the melanocortin receptor (MCR) family have previously been shown to rescue the impairment in hippocampus-dependent synaptic plasticity in the APP/PS1 mouse model of AD. However, the functional roles of MCR signaling in AD conditions, particularly in glial functions, are largely unknown. In this study, we investigated the potential benefits of MCR activation in AD. In APP/PS1 transgenic mice, we demonstrate that MCR activation mediated by the central administration of its agonist D-Tyr MTII substantially reduces Aβ accumulation, while alleviating global inflammation and astrocytic activation, particularly in the hippocampus. MCR activation prominently reduces the A1 subtype of reactive astrocytes, which is considered a key source of astrocytic neurotoxicity in AD. Concordantly, MCR activation suppresses microglial activation, while enhancing their association with amyloid plaques. The blunted activation of microglia may contribute to the reduction in the neurotoxic phenotypes of astrocytes. Importantly, transcriptome analysis reveals that MCR activation restores the impaired homeostatic processes and microglial reactivity in the hippocampus in APP/PS1 mice. Collectively, our findings demonstrate the potential of MCR signaling as therapeutic target for AD.